The effect of the information processing strategy on learning some basic skills in the ground tennis competition for young players - Tahseen, Tahseen Husni (International Journal of Psychosocial Rehabilitation, 2020)
The information processing strategies that the players use to deal with, acquire, store and retrieve information as the theoretical side, the practical side and the amount of interaction between them in order to develop the educational process and obtain better learning results in the basic skills of the tennis competition. Each learner of the players has his own cognitive style that affects his path. Its treatment of information, and that the research problem lies in the use of the information-processing strategy of preparing the number of educational units that were insufficient for the vocabulary of teaching skills for the competition, and the research aims to prepare an information-processing strategy in learning some basic skills in the tennis competition for young players, and the researcher used The experimental approach of the pre and post testing of the experimental and control groups for its suitability to the nature of the research, and the research community was determined for the players of Al-Hillah Sports Club / Babil Governorate for the tennis competition for the 2019 sports season, and their number (10 players). Control, by (five players) for each group The information processing strategy was applied for a period of eight weeks and at three training units per week. The researcher used the statistical bag (spss) to process the data. The researcher reached the most important conclusions. There is a positive effect of the information processing strategy on learning basic skills in ground tennis youth.